Pengaruh Komitmen Organisasional Dan Kecerdasan Emosional Terhadap Kinerja Pegawai Melalui Organizational Citizenship Behaviour Pada Pegawai KPP Pratama Kediri - Antonius Atet Wiyono; Eka Askafi; Nisa Mutiara (Otonomi, 2023)
This study aims to determine the influence of emotional intelligence and organizational commitment on the employee performance fashion department in Kantor Pelayanan Pajak Pratama Kediri with organizational citizenship behavior (OCB) as intervening. The population in this study were all employees working at Kantor Pelayanan Pajak Pratama Kediri and the sample used was 52 respondents. The sampling technique uses probality sampling with a simple random sampling method. The research model was tested by using the path analysis. The results of this study showed that emotional intelligence and organizational commitment had a positive effect on Organizational Citizenship Behavior (OCB). Emotional intelligence, organizational commitment, and Organizational Citizenship Behavior (OCB) had a positive effect on employee performance. Emotional intelligence and organizational commitment had an indirect effect on employee performance through Organizational Citizenship Behavior (OCB). When analyzed further, the percentage of direct effect was higher than the indirect effect, which showed that the mediating variable of Organizational Citizenship Behavior (OCB) had less effect on employee performance